EXPLORING THE LINK BETWEEN VITAMIN D DEFICIENCY AND EPILEPSY: UNRAVELING THE CONNECTION – A COMPARATIVE STUDY - Dr Kumar Jee Kaul; Dr Anuj Bagga (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective:• To determine the serum levels of 25-OH vitamin D in patients of epilepsy.• To determine magnitude of vitamin D deficiency in the study groups and to compare the study groups with control group and among themselves.Materials and Methods: The study was done on 136 patients, fulfilling the inclusion and exclusion criteria who were admitted to Govt Doon Medical College Hospital, Dehradun between September 2022 to October 2023 and serum levels of 25-OH vitamin D were measured of patients with epilepsy.Results: statistically significant (p